1995
DOI: 10.1007/bf03010713
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway involvement in Parkinson’s disease resulting in postoperative respiratory failure

Abstract: Parkinson's disease (PD) is a disorder of the extrapyramidal system resulting from the deficiency of dopamine in the basal ganglia. ~ It is characterized by bradykinesia, rigidity, rest tremour, and parasympathetic hyperactivity. Respiratory dysfunction has been noted in patients with PD and multiple causes have been proposed including impaired central control of respiration, abnormal extrapyramidal control of respiratory muscles, excessive secretions, decreased chest wall compliance, and upper airway obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 9 publications
0
21
0
3
Order By: Relevance
“…Although the rate of pneumonia was not significantly different in our patient cohort when compared to controls, it is possible that the treating physicians realized the importance of interventions, ranging from forced respiratory therapy, continuous positive airway pressure training, and frequent X-ray control of the thorax, and instituted these preventive measures. Easdown et al reported that sufficient and prompt intake of Parkinson medication positively affects not only the symptoms of PD but also improves inspiration and expiration in particular, thereby possibly decreasing the incidence of pulmonary infection [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the rate of pneumonia was not significantly different in our patient cohort when compared to controls, it is possible that the treating physicians realized the importance of interventions, ranging from forced respiratory therapy, continuous positive airway pressure training, and frequent X-ray control of the thorax, and instituted these preventive measures. Easdown et al reported that sufficient and prompt intake of Parkinson medication positively affects not only the symptoms of PD but also improves inspiration and expiration in particular, thereby possibly decreasing the incidence of pulmonary infection [10].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lethargy, rigidity, and a possible lack of coordinated control of thoracic musculature may be present [2,3]. Consequently, aspiration pneumonia is one of the most common causes of death in patients with PD [10]. Although the rate of pneumonia was not significantly different in our patient cohort when compared to controls, it is possible that the treating physicians realized the importance of interventions, ranging from forced respiratory therapy, continuous positive airway pressure training, and frequent X-ray control of the thorax, and instituted these preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…1 The anatomic alteration is located in the neurons of the extrapyramidal system, and the main clinical manifestations are rigidity and tremor. 2 Besides these neurologic alterations, respiratory dysfunction has been described in these patients due to involuntary movements of the glottis and supraglottic structures. 3 Patients with PD resistant to pharmacologic treatment may have the opportunity to undergo a therapeutic surgical procedure in an advanced stage of their illness.…”
mentioning
confidence: 99%
“…Upper airway dysfunction can cause retained secretions, atelectasis, aspiration, lower respiratory tract infections and post extubation laryngospasms [6]. The Parkinsonism-Hyperpyrexia Syndrome (PHS) can occur in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%